HUBUNGAN ANTARA OBESITAS DENGAN ARUS PUNCAK EKSPIRASI ANAK USIA 8 – 12 TAHUN DI SEKOLAH DASAR SARASWATI TABANAN - Desak Made Wahyu Ariningsih; I Made Niko Winaya; I Wayan Gede Sutadarma (Bachelor of Physiotherapy and Physiotherapy Profession Study Program, Faculty of Medicine, Udayana University in collaboration with Indonesian Physiotherapy Association (IPA), 2018)
ABSTRACT The purpose of this study was to know correlation between obesity and peak expiratory flow rate in children. This study was done in April 2017. The design of the study was correlational with the cross-sectional method. The samples in this study were obesity children in Saraswati Tabanan primary school of 8-12 years old as many as 55 samples based on consecutive sampling technique. Based on Pearson Correlation test to determine the relationship between obesity with peak expiratory flow rates the results showed a moderate negative association between obesity with peak expiratory flow rates of children with p = 0,000 and r = -0.524. This shows that the higher value of BMI obesity category in children, the lower peak expiratory flow rate value is. The results of this study shows that there was a significant relationship with moderate correlation between obesity with peak expiratory flow rate of the 8-12 year old children at Saraswati Tabanan Primary School Keywords: obesity, peak expiratory flow rate, peak flow meter